Measurement and Exposure Assessment of Intermediate Frequency Magnetic Fields From Electronic Article Surveillance (EAS) Gates in Libraries - Ikuyo, Miwa; Esaki, Kaoru; Aimoto, Atsuko; Wake, Kanako; Yamaguchi-Sekino, Sachiko; Kojimahara, Noriko; Suzuki, Yukihisa; Taki, Masao (Frontiers in Public Health, 2022)
Exposure to electromagnetic fields from electronic article surveillance (EAS) gate was evaluated in consideration of application to epidemiological studies of library workers who are exposed continually to intermediate frequency magnetic field from EAS gate. Two types of exposures were investigated. One was transient exposure due to passing through or beside the gate and another was chronic exposure in the room. We measured magnetic fields from five EAS gate models which were commonly used in libraries in Japan. Detailed measurements around the gate was performed for two gate models. Magnetic field distribution in a large room was also measured for one gate model. We developed a method to evaluate exposure level from limited information about EAS gate and working conditions based on those detailed measurements. The methodology is expected to be applied in the future epidemiological studies.